Electronic dice / Siti Aisyah Abu Bakar and Ruslina Jaafar - Abu Bakar, Siti Aisyah; Jaafar, Ruslina (2001)
The popularity of the electronic dice will be most useful in these days of electronic game and it is more enjoyable to play monopoly. It is used to generate random numbers between one to six every time the button is pressed. Electronic dice uses many component such as IC’s, resistors , capacitors, rectifier anode display and switches. The function of this module is to take the 3- bit binary output from the clock and counter module and convert it into a seven bit signal that will correctly drive the LED display with the six number that make up the ‘Electronic Dice’. This project uses common anode display where all of the outputs are common anode connected to the supply.